COMPARING THE EFFECT OF PROBIOTIC STREPTOCOCCUS SALIVARIUS K12 AND M18 ON THE STREPTOCOCCUS MUTANS COUNT, SALIVARY PH AND BUFFER CAPACITY: A RANDOMIZED DOUBLE BLINDED CLINICAL TRIAL - Saravanan Poorni; Manali Srinivasan; Nivedhitha M.s (Cumhuriyet University, 2022)
Aim: To evaluate and compare the effect of probiotic Streptococcus salivarius K12 and M18 on the Streptococcus mutans count, salivary pH and buffer capacity. Materials and method: 69 Subjects within the age group of 18-40 years were randomly allocated to three groups of 23 subjects each. Subjects enrolled in Group A received BLIS K12TM, Subjects in Group B received BLIS M18TM and Subjects in Group C belonged to the control group and did not receive any form of probiotics. Unstimulated salivary samples were collected at baseline and after 30 days. The samples were analysed for Streptococcus mutans level, salivary pH and buffer capacity. Results: A statistically significant reduction in salivary S. mutans levels and an increase in the salivary pH was observed after the use of probiotics when compared to the baseline. The buffer capacity remained unaltered following the use of both the probiotics. There was no change in the Streptococcus mutans level, salivary pH and buffer capacity for the subjects belonging to the control group. Conclusion: Within the limitations of the present study it can be concluded that a 30day use of Streptococcus salivarius K12 and M18 resulted in a reduction in the Streptococcus mutans count while simultaneously improving the salivary pH.